PENGARUH COMMUTER-RAIL RUTE JAKARTA-BOGOR TERHADAP PENGEMBANGAN KAWASAN DAN POTENSINYA DALAM MENDUKUNG TRANSIT ORIENTED DEVELOPMENT - Madigliani, Adam; Tresani, Nurahma; Winayanti, Lana; Apriyanto, Heri; Prasetya, Hermawan (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
This study examines the impact of the Jakarta-Bogor commuter rail line on the intensity of residential area development around the stations and its potential in supporting transit-oriented development in the future. The research highlights the crucial role of the commuter train in integrating various regions, creating networks that influence regional development, particularly in areas around the stations. Qualitative methodology is employed, including field observations and semi-structured interviews with stakeholders such as real estate developers, property agents, and government institutions. The findings indicate that the commuter train significantly affects the development of low-density housing around the stations. This underscores the need for government oversight to manage the rapid urbanization in these areas by promoting the realization of high-density residential areas supported by various spatial functions, as prerequisites for Transit-Oriented Development (TOD) in the Jabodetabek region. The study recommends revising spatial planning around the stations to encourage a synergistic approach between public transportation and urban area development, as well as urban redevelopment or revitalization.